Realization of the kilogram by the XRCD method. (28th September 2016) - Fujii, Kenichi; Bettin, Horst; Becker, Peter; Massa, Enrico; Rienitz, Olaf; Pramann, Axel; Nicolaus, Arnold; Kuramoto, Naoki; Busch, Ingo; Borys, Michael
Abstract: When the kilogram is redefined in terms of the fixed numerical value of the Planck constant h, the x-ray-crystal-density (XRCD) method, among others, is used for realizing the redefined kilogram. The XRCD method has been used for the determination of the Avogadro constant N A by counting the number of atoms in a 28 Si-enriched crystal, contributing to a substantial reduction of uncertainty in the values of N A and h to 2 parts in 10 8 . This method can be therefore used reversely for the mass determination of a 1 kg sphere prepared from the crystal. This is realized by SI-traceable measurements of its lattice parameter, isotopic composition, volume, and surface properties. Details of the corresponding measurements are provided, as well as the concept of the XRCD method, isotope enrichment, crystal production, sphere manufacturing, and evaluation of impurities and self-point defects in the crystal, together with mass comparison with respect to the silicon sphere for disseminating mass standards.